The role of IL-6 receptor inhibitor treatment in critical patient monitoring with COVID-19 - (:unkn) unknown (MRE PRESS, 2021)
Objectives: The COVID-19 disease can manifest itself with acute respiratory distress syndrome, renal failure. and septic shock in critically ill patients. There are opinions that there is a correlation between high IL-6 levels and disease severity. In our intensive care unit, we evaluated the changes in the laboratory data and radiological involvement severity of our patients who underwent tocilizumab treatment and examined the appropriate laboratory parameter in the treatment follow-up and its effect on survival. Methods: In the critical patient follow-up of COVID-19, 17 of the 23 patients treated with tocilizuniab had a mortal course (Group 1) and the remaining 6 (Group 2) were. The C-reactive protein, lactate dehydrogenase, IL-6, D-dimer. procalcitonin, albumin. and ferritin values, which were routinely screened in our clinic on the day of tocilizumab treatment and the 5th day after, were recorded. Both the change between the two groups and the change between days 1 and 5 were analyzed. Results: A total of 23 patients (55.35 +/- 13.31 years) were included in the study. The computed tomography severity score assessed at the intensive care unit admission was statistically significantly higher in Group 2. The procalcitonin and lactate dehydrogenase values measured on day 5 after tocilizumab were significantly lower in Group 2. On the 5th day after treatment, the levels of C-reactive protein, ferritin, chest X-rays, IL-6 and D-dirner statistically significantly changed compared to the first day of the treatment. In correlation with the decrease in PCT as of the 5th day after tocilizumab administration. an increasing tendency was observed in 28-day survival. Conclusion: This study demonstrated that tocilizumab treatment may positively contribute to the treatment by decreasing cytokine levels. PCT and LDH follow-up before and after treatment in critically ill patients who are receiving tocilizumab treatment can give an idea about survival.
Keywords: Coronavirus; IL-6 receptor inhibitor; Intensive care units; Tocilizumab; LDH; PCT; CRP